2023
DOI: 10.1007/s43615-023-00263-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Awareness of Plastic: an Overview of Different Research Areas

Abstract: Plastic makes our society more practical and safer. It is hard to consider eliminating plastic in some sectors, such as the medical field. However, after use, plastic waste becomes a global problem without precedents, and when not properly disposed of, it can cause several socio-environmental problems. Some possible solutions are recycling, the circular economy, proper waste management, and consumer awareness. Consumers play a crucial role in preventing problems caused by plastic. In this work, consumer awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…, 2021b; Huang et al. , 2022); on the other hand, it may also be due to the lack of consumers' environmental awareness (de Sousa, 2023) and their inability to realize the serious consequences of “greenwashing” on the environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021b; Huang et al. , 2022); on the other hand, it may also be due to the lack of consumers' environmental awareness (de Sousa, 2023) and their inability to realize the serious consequences of “greenwashing” on the environment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mediating role of "perceived greenwashing" was not confirmed, which doesn't support H6 and H7, probably due to the fact that "perceived greenwashing" is an exotic term and Chinese consumers are not familiar with its concept (Zhang et al, 2021b;Huang et al, 2022); on the other hand, it may also be due to the lack of consumers' environmental awareness (de Sousa, 2023) and their inability to realize the serious consequences of "greenwashing" on the environment.…”
Section: Consumermentioning
confidence: 86%
“…Finally, consumer behavior and awareness are key factors. Despite growing public awareness of plastic pollution, many consumers do not know how to properly dispose of and recycle plastics [57]. There is a significant need for educational initiatives and incentive programs to encourage consumer participation in recycling programs [58].…”
Section: Challenges and Solutions In Plastic Recyclingmentioning
confidence: 99%
“…de Sousa (2023) found that there is a gap between consumer awareness and behavior regarding plastic waste, and that different research areas have different focuses and approaches to address the plastic problem. Scholars also identified some research gaps and opportunities for future studies.…”
Section: Introductionmentioning
confidence: 99%